2014
DOI: 10.1017/s0025315414000022
|View full text |Cite
|
Sign up to set email alerts
|

The effects of seasonal variation on the nutritional condition ofNephrops norvegicus(Astacidea: Nephropidae) from wild populations in the western Mediterranean

Abstract: The Norway lobster, Nephrops norvegicus is a target fishery species in European waters. The stock assessment of N. norvegicus is complicated because it is caught in commercial gear only when it emerges from its burrow. Landings are lower in winter, and feeding limitations have been hypothesized as the cause. Wild large-sized male lobsters were sampled each season (winter, spring, summer and autumn), and two groups of animals were kept in captivity for 90 d (fed and fooddeprived). The hepatopancreas and muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
2
1
0
Order By: Relevance
“…Although the sexes have similar diets, as shown in the present study, the overall opportunity for feeding may be reduced in females. However, starvation and sex-specific reduction in nutritional status has been previously examined and found to be absent 10 , with corroborating evidence from biochemical markers that suggest good nutritional condition throughout the year in females 38 . Although Clew Bay is a particularly shallow site, the same major food groups (i.e.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although the sexes have similar diets, as shown in the present study, the overall opportunity for feeding may be reduced in females. However, starvation and sex-specific reduction in nutritional status has been previously examined and found to be absent 10 , with corroborating evidence from biochemical markers that suggest good nutritional condition throughout the year in females 38 . Although Clew Bay is a particularly shallow site, the same major food groups (i.e.…”
Section: Discussionsupporting
confidence: 57%
“…Due to their burrowing lifestyle and long breeding season in females, much effort has gone into investigating seasonal starvation in Nephrops 10,[37][38][39] . The ability to feed on particulate food sources would help to counteract starvation brought about by these lifestyle restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…While in general GSI has been shown to clearly change seasonally in relation to the maturation state of the female gonads [5,24], HSI and the percentage of lipid in the hepatopancreas has been shown to be more variable. For instance, in some studies [25] lipid content in the hepatopancreas has been reported not to change significantly with season, while in other studies conducted in the Clyde Sea area [26] the lowest levels were obtained in the spring, which is similar to the present study. The earlier increase in HSI observed in females should then be explained by an increase in other constituents, such as water content [23] rather than an increase in lipid content.…”
Section: Discussionsupporting
confidence: 89%